Perancangan Sistem Penyiraman Tanaman Otomatis - Muhammad Ridwan (Politeknik Kampar, 2021)
Fertile soil is a prerequisite for plants to grow well. Fertility level can be influenced by the intensity of the water it contains. In order for plants to grow properly, watering needs to be done every time and continuously. This tool aims to replace manual work to automatic. The benefit of this tool is that it can facilitate human work in watering plants. This tool uses a soil moisture sensor that functions as a soil moisture detector and sends commands to Arduino nano to turn on the relay driver so that the pump can flush water according to the needs of the soil automatically.